2009
DOI: 10.1007/s10886-008-9580-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Pheromone-Based Trapping Method for the Banana Root Borer Cosmopolites sordidus

Abstract: The banana root borer Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae) is a major pest of bananas throughout the world. Chemical control is both undesirable and expensive, where biological control alternatives are limited, and pheromone-based trapping results in low captures. In this study, several important factors that affect pheromone-based catches, such as trap type, trap dimensions, and color and position of the traps, were optimized. Ground traps were found to be superior to ramp and pitfall tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…The male-produced aggregation pheromone sordidin attracts both sexes, and mass trapping by using ground traps has the potential to replace inefficient insecticide treatments (Reddy et al 2009). …”
Section: Practical Use Of Mass-trappingmentioning
confidence: 99%
“…The male-produced aggregation pheromone sordidin attracts both sexes, and mass trapping by using ground traps has the potential to replace inefficient insecticide treatments (Reddy et al 2009). …”
Section: Practical Use Of Mass-trappingmentioning
confidence: 99%
“…Conversely, it is important to emphasize that for the successful management of the banana root borer, the establishment of multiple control strategies is needed. This include a focus on increasing plant diversity (DASSOU et al, 2015), biological control through the use of entomopathogenic fungi (AKELLO et al, 2008;LOPES et al, 2013), and the use of pheromones to capture adult pests (REDDY et al, 2009;ALPIZAR et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In banana orchards, studies of the management of C. sordidus have shifted to implementing microbial (AKELLO et al, 2008;LEMA-LÓPEZ et al, 2010;PAULI et al, 2011;FANCELLI et al, 2013;LOPES et al, 2013) and behavioral control (REDDY et al, 2009;ALPIZAR et al, 2012), as well as, more recently, environmental management (DASSOU et al, 2015). To expand the options for adequate pest management, researchers showed that planting bananas with genotypes that confer different levels of pest resistance to the plant is a possible strategy for management of the banana weevil.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the efficacy of sordidinbaited pitfall traps (Tinzaara et al, 1999;de Graaf et al, 2005). A more recent study demonstrated that crawl-in ground traps outperform pitfall traps (Reddy et al, 2009), and that traps are more effective in the shade (Reddy et al, 2008(Reddy et al, , 2009). Reddy's group also has shown that brown or black pitfall traps are more efficacious than other colors (Reddy and Raman, 2011).…”
Section: Introductionmentioning
confidence: 93%